2019
DOI: 10.1186/s13100-019-0159-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of charged amino acids required for nuclear localization of human L1 ORF1 protein

Abstract: Background Long Interspersed Element 1 (LINE-1) is a retrotransposon that is present in 500,000 copies in the human genome. Along with Alu and SVA elements, these three retrotransposons account for more than a third of the human genome sequence. These mobile elements are able to copy themselves within the genome via an RNA intermediate, a process that can promote genome instability. LINE-1 encodes two proteins, ORF1p and ORF2p. Association of ORF1p, ORF2p and a full-length L1 mRNA in a ribonucleop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 89 publications
(164 reference statements)
1
20
0
Order By: Relevance
“…It contains a bi-directional promoter in the 5′UTR; two open reading frames, namely ORF1 and ORF2, and a 3′UTR with a polyadenylation signal (polyA) (Figure 1) [12][13][14]. ORF1 encodes a ~40 kD protein with the chaperone activity necessary to stabilize a new L1 copy [15][16][17][18]. ORF2 encodes ~150 kD proteins with the endonuclease and retrotransposase activity required for the retrotransposition process [15,19,20].…”
Section: L1 Structurementioning
confidence: 99%
See 2 more Smart Citations
“…It contains a bi-directional promoter in the 5′UTR; two open reading frames, namely ORF1 and ORF2, and a 3′UTR with a polyadenylation signal (polyA) (Figure 1) [12][13][14]. ORF1 encodes a ~40 kD protein with the chaperone activity necessary to stabilize a new L1 copy [15][16][17][18]. ORF2 encodes ~150 kD proteins with the endonuclease and retrotransposase activity required for the retrotransposition process [15,19,20].…”
Section: L1 Structurementioning
confidence: 99%
“…Transportation of L1 RNP from the cytoplasm to the nucleus is accomplished using the membrane-associated endosomal sorting complex required for transportation (ESCRT) [30]. It has also recently been shown that the ORF1 protein interacts with the KPNA2 and KPNB1 karyopherins, as well as possibly other KPNA family proteins involved in nuclear protein importation through nuclear pores (nuclear pore complex) [18]. The cancer cell model showed that L1 RNP penetrates the nucleus during mitosis and the integration of the new copy of the L1 element into the genome occurs in the S phase of a cell cycle [31].…”
Section: Retrotransposition Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitation of homology-based methods is more pronounced in cases where no homology is found between the query sequence and the annotated proteins sequence. Additionally, it is known that a single amino acid substitution in localization signals can change the localization of a protein [ 25 , 26 , 27 ]. Thus, sequence homology is a noncausal feature for the localization prediction and should be used with caution when applied to nonnative sequences or in case when homology is less [ 28 ].…”
Section: Computational Approaches For Protein Localizationmentioning
confidence: 99%
“…L1 proteins interact with L1 RNA to facilitate the assembly of L1 ribonucleoproteins (RNPs). The entry process by which L1 RNPs move from the cytoplasm into the nucleus is dependent on the nuclear localization signal on L1 ORF1p ( Freeman et al, 2019 ). Upon entering the nucleus, L1 ORF2p uses its nuclease activity to form a single chain gap on genome DNA, and then uses its RT activity, with the single chain gap DNA as the primer and L1 mRNA as the template, to start the reverse transcription ( Kazazian and Moran, 1998 ; Goodier, 2016 ).…”
Section: Introductionmentioning
confidence: 99%